Menstruation: An Ableist Narrative - Nair, Prianka (Columbia Journal of Gender and Law, 2021)
This essay outlines how the focus on able-bodied menstruators in the development of social narratives about menstruation erases the experiences and the discrimination experienced by menstruators with disabilities. Many menstruators with disabilities experience shame around menstruation, embarrassed about the “burden” of their menstrual experiences on their caregivers and concerned about breaching menstrual etiquette around hygiene. Narratives about menstruation are incomplete without considering these experiences. Introducing a disability perspective also permits us to interrogate why popular depictions of the menstruating body are inadequate, how they continue to reinforce and romanticize values like independence and productivity, and validate structures that grant power and privilege to those values. Finally, the essay introduces ideas like supported decision-making and dismodernism that center the experiences of individuals with disabilities. This shift in focus has the potential to transform menstrual activism by introducing into the conversation more nuanced values of reciprocity, interdependence, and empathy.